Warum wächst die Wirtschaft in Österreich rascher als in Deutschland? - Fritz Breuss (Austrian Institute of Economic Research (WIFO), 2006)
– Germany and Austria, neighbours of different size and with the same language, still have close economic bonds, but the combined effect of Austria joining the EU, the eastern opening and the EU's enlargement has made Austria grow increasingly separate from Germany. Since the early 1990s, Austria's economic growth rate has been surpassing the German equivalent by percentage point per year. The reasons for this are manifold, but appear to be chiefly in the burden attending German reunification. Also, the German business sector seems to have been less able than its Austrian counterpart to tap the new opportunities springing from Europe's progressing integration (internal market and currency union) and the EU's enlargement. Already the eastern opening opened up a new "window of opportunity" for Austria which the economy made full use of. In part, the asymmetric architecture of EMU's macropolicy (excessive real interest rates, fiscal rules of the stability and growth pact) appears to pose greater problems for Germany than for Austria. Lastly, the negative structural effects of globalisation (outsourcing, etc.) may have been a reason for Germany's weak growth. However, since the globalisation effect also applies to Austria, the growth gap between the two countries cannot be explained by this hypothesis.
Keywords: 330; Deutschland; Österreich; Wirtschaftsvergleich; Globalisierung; Wirtschaftswachstum; Vergleich; Deutschland; Österreich